Dynamical analysis of multilayered reinforced composite cylindrical shells - Bich, Dao Huy; Tuan, Tran Thanh (Vietnam Journal of Mechanics, 2005)
In the present paper the governing dynamical equations for multilayered reinforced composite cylindrical shells based on Kirchhoff-Love's theory and Lekhnitsky's smeared stiffeners technique are derived. The shell is reinforced by longitudinal and ring stiffeners. The longitudinal stiffeners may be composite or sleeves with SMA wire. The linear problem of shell vibration is considered for illustrating the effects of the stiffeners, the shell geometry and altering the lamination scheme on fundamental frequencies of the shell.